Cortical dendritic activity correlates with spindle-rich oscillations during sleep in rodents - Julie Seibt (Nature Portfolio, 2017)
Different stages of sleep, marked by particular electroencephalographic (EEG) signatures, have been linked to memory consolidation, but underlying mechanisms are poorly understood. Here, the authors show that dendritic calcium synchronisation correlates with spindle-rich sleep phases.